Madā Inqirāiyyati Kitāb Durus al-Lughah Li ash-Shaff al-Awwal bi Ma’hadi Dārissalam Gontor - Ahmad Zaki Annafiri; Hisyam Zaini (University of Darussalam Gontor, 2022)
This study aims to determine the readability level of the Durusullughah Al-Arabiyyah book and determine the percentage of common words in the Durusullughah Al-Arabiyyah book and its relationship with the readability level of the book. This study uses a mix-method approach (qualitativequantitative), with a descriptive presentation. The primary sources of this research are the result of the Cloze Test against the Durusulluguhah AlArabiyyah book and the Al-Munawwir Dictionary, with secondary sources in the form of books, articles, and other reliable references. The results showed that 235 sample people answered 100 points of the Cloze Test with a truth level of 75%, this level indicates the intermediate level or teaching level. The comparison of words in the Cloze test text with words in the AlMunawwir dictionary shows 96%. This figure shows that 96% percent of the words in the Cloze test text that represent the book Durusullughah, are in al-Munawwir’s dictionary. The high percentage of common words in a book indicates a high level of readability of the book. It can be concluded, that the book Durusullughah Al-Arabiyyah is a textbook that is easy to learn by students who use the Al-Munawwir Dictionary for daily learning.